2020
DOI: 10.1590/2175-8239-jbn-2018-0232
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the serial changes in measurements of renal allograft Doppler resistive index in the first postoperative month

Abstract: Introduction: The role of single Doppler-derived renal resistive index (RI) in renal allograft management is still a controversial issue, however detection of changes in serial duplex scanning has been reported as more valuable. This study aimed to test the hypothesis that early change in RI following transplantation may be related to factors associated with delayed graft function (DGF). Material and methods: 113 patients were included, in whom two RI measurements were performed within 30 days post-transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In this issue, Moura-Neto et al 1 evaluated the role of serial RI in the immediate postoperative period to assess delayed graft function due to ischemia-reperfusion injury in 113 renal transplant patients. The study excluded patients with histology-proven acute rejection, hydronephrosis of grade 2 or higher, and peritransplant collections causing marked compression, as these conditions may also cause elevated RIs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, Moura-Neto et al 1 evaluated the role of serial RI in the immediate postoperative period to assess delayed graft function due to ischemia-reperfusion injury in 113 renal transplant patients. The study excluded patients with histology-proven acute rejection, hydronephrosis of grade 2 or higher, and peritransplant collections causing marked compression, as these conditions may also cause elevated RIs.…”
mentioning
confidence: 99%
“…This is consistent with studies that have shown RI elevation on immediate postoperative Doppler ultrasound as a predictor of acute tubular necrosis (ATN) and delayed graft function 2 , 3 . While most studies evaluate RI on a single early postoperative Doppler ultrasound, Moura-Neto et al 1 incorporated two serial measurements of RI over four weeks and evaluated interval change. This approach of analyzing change over serial studies has been used by other authors and may be more reflective of the allograft characteristics than a single measurement, particularly in the early postoperative period.…”
mentioning
confidence: 99%
See 1 more Smart Citation